Typology of cognitive processes. A tool for educational analysis - Manrique, María Soledad (2020)
The work is based on the need of every education professional to become an educational analyst. It summarizes and explains a series of analysis categories that allow educational phenomena to be approached from a cognitive perspective. It starts with a general introduction about cognition and different lines from which it can be addressed. Then the lower and upper cognitive processes are described. It is expected that the typology of processes provided will be a valuable tool for the analysis of teaching situations.